2019
DOI: 10.1093/ibd/izz202
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab and Adalimumab Concentrations May Vary Between the Enzyme-Linked Immunosorbent Assay and the Homogeneous Mobility Shift Assay in Patients With Inflammatory Bowel Disease: A Prospective Cross-Sectional Observational Study

Abstract: This prospective observational study including consecutive patients with inflammatory bowel disease treated with either infliximab or adalimumab showed that although the correlation between the ELISA and the homogeneous mobility shift assay was good for both drugs, the agreement was poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…8 The difference in the numbers could be related to difference in IFX concentration detection assays used. 19,20 In addition to what was found in the PANTS study, we demonstrated that patients who had an infusion-4 level of ≥5 µg/mL had a 90% decrease of FCP from baseline to infusion 4 by, whereas patients with an IFX< 5 µg/mL had only a 35% decrease after induction.…”
Section: Discussionsupporting
confidence: 76%
“…8 The difference in the numbers could be related to difference in IFX concentration detection assays used. 19,20 In addition to what was found in the PANTS study, we demonstrated that patients who had an infusion-4 level of ≥5 µg/mL had a 90% decrease of FCP from baseline to infusion 4 by, whereas patients with an IFX< 5 µg/mL had only a 35% decrease after induction.…”
Section: Discussionsupporting
confidence: 76%
“…We also found that infliximab and adalimumab concentrations before and after the correction of the HMSA were significantly different, both quantitatively and qualitatively. This is in line with previous studies showing discrepancies among assays used for evaluating biologic drug concentrations [8,9,14,15]. Moreover, we identified adalimumab concentration thresholds of 22.4 µg/mL before the corrected measures and 14.4 µg/mL after the corrected measures discriminated patients with or without treatment failure.…”
Section: Discussionsupporting
confidence: 91%
“…However, these thresholds can vary depending on the targeted clinical outcome, IBD phenotype, and TDM assay used [7]. Regarding the latter, we have previously shown a discrepancy between a commercially available enzyme-linked immunosorbent assay (ELISA) and a commercially available homogeneous mobility shift assay (HMSA), for both infliximab and adalimumab concentrations [8,9]. Based on these results, a comprehensive review of the HMSA assays was initiated and an upward drift for both infliximab (from December 2017 to May 2019) and adalimumab (from August 2017 to May 2019) was found, including the period during which our study was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although a comparison of commercially available homogenous mobility shift assay and ELISA to assess infliximab and adalimumab concentrations found good correlation between the assays for each biologic (infliximab: r = 0.861; P < 0.001; adalimumab: r = 0.935; P < 0.001), agreement between the assays was weak (infliximab intraclass correlation coefficient = 0.356 [95% CI, −0.069 to 0.720]; P < 0.001; adalimumab intraclass correlation coefficient = 0.395 [95% CI, −0.073 to 0.759]; P < 0.001). 13 Therefore, if the aim is to establish whether a particular cutoff concentration of a TNF antagonist has been reached as part of a TDM approach, it is always recommended to select the assay that was initially used to establish the respective threshold.…”
Section: Tdm Of Tnf Antagonists In CDmentioning
confidence: 99%